PENGARUH JENIS PELARUT DAN SUHU PENGERINGAN TERHADAP KARAKTERISTIK EKSTRAK PADA BUAH KELUBI (Eliodoxa conferta) - Atisanto, Victory Sandy; Mulyani, Sri; Lani Triani, I Gst. Ayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 3 (2017): September, 2017)
The purposeS of this study was (1) to determine the effect of solvent and drying temperature on the characteristics of kelubi fruit extract, (2) to obtain the solvent and the drying temperature to produce the kelubi fruit extract with the best characteristics. The experiment used a randomized block design with two factors. The first factor was of drying temperature of 55°C, 60°C, and 65°C. The second factor was ethanol and ethyl acetate solvent concentration. The results showed the best treatment was ethanol solvent and temperature 55 ° C with the extract characteristics: average yield 48,91%, water content 13,53%, vitamin C 99,73 mg/100g , total phenolic 567.33 mg GAE/100g, , pH 2.34, and total acid 199.62 mg/100g. Key words: drying temperature, ethanol, ethyl acetate, kelubi, extract